2008
DOI: 10.1111/j.1540-8175.2008.00638.x
|View full text |Cite
|
Sign up to set email alerts
|

Amorphous Calcific Tumor of the Mitral Annulus Echocardiographically Mimicking a Vegetation

Abstract: We describe echocardiographic findings in an elderly patient with histologically proven amorphous tumor involving the posterior mitral annulus, mimicking a vegetation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…In contrast, Lewin et al (2) and Kubato et al (6) described cardiac CAT as late-phase chronologic changes in a thrombus and reported abnormal calcium metabolism due to renal dysfunction and suggested that inflammation associated with hemodialysis may contribute to rapid growth and pathologic changes. Histologic findings in our patients were thrombus with angiogenesis, fibrin, and calcium deposition, as reported in a literature review (4)(5)(6)(7)14).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In contrast, Lewin et al (2) and Kubato et al (6) described cardiac CAT as late-phase chronologic changes in a thrombus and reported abnormal calcium metabolism due to renal dysfunction and suggested that inflammation associated with hemodialysis may contribute to rapid growth and pathologic changes. Histologic findings in our patients were thrombus with angiogenesis, fibrin, and calcium deposition, as reported in a literature review (4)(5)(6)(7)14).…”
Section: Discussionsupporting
confidence: 78%
“…Kawata et al (21) described CATs that involve the mitral annulus as MAC-related CATs, which are considered to be a subgroup of CATs (4-6). We had three patients with a MAC-related CAT appearance, one of whom shared similar features with the patients described in the literature (4)(5)(6)21). These three and another one patient aged 27 years had chronic kidney disease; thus, patients with end-stage renal disease could be speculated to have an increased risk of MAC-related CAT or just CAT.…”
Section: Discussionsupporting
confidence: 54%
“…2,3 All patients suffered from end-stage renal disease, and the CATs were highly mobile and appar- ently mimicked valve vegetation. Although MAC-related CAT is considered to be a subgroup of CAT, these features are not common in CATs originating from other sites.…”
mentioning
confidence: 99%
“…Reynolds et al originally described calcified amorphous tumors (CATs) as endocardially based, non‐neoplastic cardiac masses. CATs can arise in any cardiac chamber and also from the mitral valve in some cases; CATs may be pedunculated or present as larger, more complex structures involving the papillary muscles or chordal apparatus.…”
Section: Subtypes Of Pseudotumorsmentioning
confidence: 99%
“…No data exist regarding superiority of one approach over the other, although surgery should be given higher regard if the patient has a high preexisting stroke risk. 52,53 Calcified Amorphous Tumor: Reynolds et al 55,56 originally described calcified amorphous tumors (CATs) as endocardially based, non-neoplastic cardiac masses. CATs can arise in any cardiac chamber and also from the mitral valve in some cases; CATs may be pedunculated or present as larger, more complex structures involving the papillary muscles or chordal apparatus.…”
Section: Mitral Annular Calcificationmentioning
confidence: 99%